Comparison of Magnetic Auriculotherapy, Laser Auriculotherapy and Their Combination for Treatment of Insomnia in the Elderly: A Double-Blinded Randomised Trial. (21st May 2019) - Suen, Lorna K. P.; Molassiotis, A.; Yueng, S. K. W.; Yeh, C. H.
Abstract : Background . Insomnia is common amongst the elderly. With the adverse effects of prolonged use of hypnotics, the exploration of noninvasive and nonpharmacological complementary methods for insomnia is warranted. Auriculotherapy (AT) is a therapeutic approach where specific points on the auricle are stimulated to manage various physiological disorders. The purpose of this study is to determine the desirable treatment modality using AT to improve the sleep conditions of the elderly. Methods . A three-arm double-blinded randomised trial was conducted on 145 eligible subjects. This study investigated three minimally invasive procedures, namely, laser auriculotherapy (LAT), magneto-auriculotherapy (MAT), and their combination. Seven auricular points were used. Treatment was performed three times a week, for six weeks. Subjects were assessed at baseline, six weeks, and follow-up after six weeks, three months, and six months. Generalised estimating equations were used to evaluate interactions amongst the groups over time based on the Pittsburgh Sleep Quality Index (PSQI), sleep parameters using actigraphic monitoring, health-related quality of life (HRQOL) using SF-12, and PHQ-9 for depression status. Results . The treatment effects of the three procedures were comparable. Significant improvements were found in all of the subjective measures (PSQI, HRQOL, and PHQ-9) for individual groups over time. Improvements in the objective sleep parameters using actigraphic monitoring were detected in subjects who received MAT procedures but not in those who received LAT. The combined MAT and LAT approach did not show any advantage over MAT. Conclusions . The treatment effects of the three procedures were comparable in subjective parameters but not by objective measures using actigraphic monitoring. Longer therapeutic course and more frequent administration of LAT may be considered in future trials to achieve the optimal treatment effect. Trial Registration . This trial is registered with ClinicalTrials.gov:NCT02970695, registered May 2016.